STUDI EKSEGETIS MAKNA PASANGAN SEIMBANG DAN TIDAK SEIMBANG BERDASARKAN 2 KORINTUS 6:14-16 - Daniel Sarwono (Sekolah Tinggi Teologi Arastamar Bengkulu, 2015)
A balanced life partner is very important because there are many different things that are found in the person of a believer and an unbeliever. God Himself establishes a suitable life partner that is not unbalanced. God knows that man His creation will need a balanced partner, therefore our partners are in God's hands, but very often when we choose an unbalanced life partner, we say that this is my partner from God, when in fact we are choosing by ourselves because there are some things that we pay attention to with our partners that can make us happy, we don't realize that it is only temporary, so we don't care anymore, whether it's balanced or not, what matters is my partner who is from God. Through this paper, we try to give a biblical explanation of a balanced and unbalanced partner to give insight to the believer in thinking about his life partner.